2020
DOI: 10.3390/cancers12061552
|View full text |Cite
|
Sign up to set email alerts
|

Should the Number of Metastatic Pelvic Lymph Nodes Be Integrated into the 2018 Figo Staging Classification of Early Stage Cervical Cancer?

Abstract: Introduction: Lymph node status has become part of the new staging system for cervical cancer (CC). It has been shown that patients staged as IIIC1 had heterogeneous prognoses and, in some cases, experienced better outcomes than patients with lower stages. We evaluated the impact of the number of metastatic pelvic lymph nodes (MPLNs) among patients with stage IIIC1 cervical cancer. Methods: Survival analyses were conducted in order to identify the best cut-off prognostic value relative to the number of MPLNs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 45 publications
1
35
0
Order By: Relevance
“…To date, data on burden of nodal disease in cervical cancer are limited. In studies of patients with early-stage cervical cancer treated with radical surgery followed by radiotherapy, some authors showed that the survival difference between patients with 1 and ≥ 2 pelvic pLN(s) was statistically significant (8). On the other hand, Tsai et al (13) reported that patients with only one pLN had achieved similar outcomes compared to pN0, and patients with ≥ 2 pelvic pLNs had lower survival rates (87% vs. 61%, p < 0.001) than those with pN0.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, data on burden of nodal disease in cervical cancer are limited. In studies of patients with early-stage cervical cancer treated with radical surgery followed by radiotherapy, some authors showed that the survival difference between patients with 1 and ≥ 2 pelvic pLN(s) was statistically significant (8). On the other hand, Tsai et al (13) reported that patients with only one pLN had achieved similar outcomes compared to pN0, and patients with ≥ 2 pelvic pLNs had lower survival rates (87% vs. 61%, p < 0.001) than those with pN0.…”
Section: Discussionmentioning
confidence: 99%
“…It is found that women with stage IIIC1 had superior cervical cancerspecific survival compared to those with stage IIIA-B disease, and varied significantly depending on various factors, such as T-stage, LN burden, etc. (3,(6)(7)(8). Nodal involvement alone seems inadequate as the sole pathologic factor to predict survival and relapse rates.…”
Section: Introductionmentioning
confidence: 99%
“…Patients of FIGO stage IIIC1-IIIC2 in the LRH group have obviously worse PFS and OS than the ORH group, but which was not statistically significant. The reasons may be as follows: first, number of patients in the subgroup was limited, especially in the LRH group; second, though lymph node metastasis is an important factor associated with the prognosis of cervical cancer patients, stratifying the clinical stage according to the lymph node status individually is still controversial (46). If the local extent of the disease between the groups was not comparable, outcomes of the surgery might also be affected.…”
Section: Analysis Of Survival Factorsmentioning
confidence: 99%
“…It is well established that lymph node metastasis is one of the most significant prognostic factors in cervical cancer [ 2 , 3 ]. Moreover recently, the number of metastatic lymph nodes has recently been shown to have an essential prognostic impact [4] . Therefore, the information on lymph node status becomes of paramount importance.…”
mentioning
confidence: 99%